ERROR IN DESCRIPTIVE TEXT OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT - Saputra, Ulil Hadi Atma; Arifin, Adip; Harida, Ratri (Jurnal Bahasa dan Sastra, 2022)
English plays an important role as a means of communication among people in the world. When Indonesian people want to comunicate in, Indonesian people must learn English language structure. Because English structure is different from Indonesian structure, it may be difficult to learn for Indonesian. So, they make an errors. This script aimed to know the commons errors and sources of error made in descriptive text by the fourth semester students of English Education Department STKIP PGRI Ponorogo. In this research, the researcher used descriptive method which intended to describe how far the students make errors in writing descriptive text. The research carried out on June- July 2018. In this research, the writer took 6 students as the subject. To collect the data, the writer used text and error analysis. The writer limited the study of analysis on the commons errors and sources errors using Corder and Brown’s theory. The result of the study showed that there were 108 errors in their descriptive text writing. The writer found the highest errors was in verb tense and the lowest errors was errors in capitalization. The writer found the sources of errors by the students was intralingual transfer.